Процесс формования порошковой стали ЭП-823: роль легирующих элементов и давления прессования - Горобец П. А.; Рудаков А. Д.; Васильева И. Э. Инесса Эдвиновна; Ваулина О. Ю. Ольга Юрьевна (Функциональные материалы, 2024)
Текстовый файл